Factors of determinism, uncertainty and stochasticity in stock and commodity markets - Safiullin Nail; Safiullin Bulat; Schnaider Olga (E3S Web of Conferences, 2019)
One of the main methodological principles of modern economics is the separation of the positive and normative study area. Traditionally, the dominant regulatory approach is associated with a "pre-scientific" era - with the economic views of antiquity and the Middle Ages. Thus, the very evolution of the economic analysis can be considered as a process of gradual replacement of a regulatory elements and achieve ever greater degree of objectivity of research. In this paper, the economic theory of multi-dimensional stock and commodity market in the green economy is considered in detail. The current state of the theory of markets and market mechanisms is discussed. The research methodology and theory of multi-dimensional stock and commodity market in the green economy, adapted to the real conditions of the transformation of the Russian economy, are substantiates. Various forms of heterogeneity of market processes are identified and classified, including factors of demand, supply and competitiveness arising from the terms of the transformation of the economy attracting green investment.